Optimization of Mechanochemical Surface Modification Parameters on Planetary Mill Using an I-Optimal Experimental Design - Ozdemir, Akin; Ucurum, Metin (Elsevier, 2024)
Several micro -particle -size additives and filler minerals are added to many industrial products, especially plastic, in order to reduce cost and improve mechanical properties and appearance. Also, grinding and surface modification are two fundamental properties of the filler minerals used in plastic products. Notably, Bayburt stone (BS) used as a natural raw material from Bayburt, Turkiye contains 76% SiO2 and 15% Al2O3. In this paper, the hydrophilic surface structure of micronized Bayburt stone (MBS) was made hydrophobe by mechanochemical surface modification using calcium stearate [Ca(C17H35COO)2] in a laboratory -type planetary mill. Next, the optimum conditions of the surface modification design factors, which are (1) ball filling ratio = 30.53%, (2) powder filling ratio = 10.43%, (3) mill speed = 475.91 rpm, (4) chemical dosage = 1.99% of powder, and (5) modification time = 4.83 min., were obtained using the proposed I -optimal design -focused optimization model when predicting the model parameters. In addition, a coated micronized Bayburt stone (CMBS) product with an active ratio (AR) of 99.90% and d10, d50, and d90 values of 1.32 mu m, 3.48 mu m and 9.55 mu m were achieved. Finally, particle size distribution (PSD), thermo-gravimetric and differential thermal analyzer (TG -DTA), Fourier transform infrared (FTIR), scanning electron microscope (SEM), electron dispersive spectrum (EDS), and contact angle analyses were performed on the CMBS product.
Keywords: Planetary Mill; Mechanochemical; Surface Modification; I-Optimal Experimental Design; Bayburt Stone